Optimal blending of multiple independent prediction models - Taraba, Peter (Frontiers in Artificial Intelligence, 2023)
We derive blending coefficients for the optimal blend of multiple independent prediction models with normal (Gaussian) distribution as well as variance of the final blend. We also provide lower and upper bound estimation for the final variance and we compare these results with machine learning with counts, where only binary information (feature says yes or no only) is used from every feature and majority of features agreeing together makes the decision.